Preventing enduring behavioural problems in young children through early psychological intervention (Healthy Start, Happy Start): study protocol for a randomized controlled trial - Ramchandani, P; O'Farrelly, C; Babalis, D; Bakermans-Kranenburg, M; Byford, S; Grimas, E; Iles, J; van IJzendoorn, M; McGinley, J; Phillips, C; Stein, A; Warwick, J; et al. (BioMed Central, 2017)
Behavioural problems are common in early childhood, and can result in enduring costs to the individual and society, including an increased risk of mental and physical illness, criminality, educational failure and drug and alcohol misuse. Most previous research has examined the impact of interventions targeting older children when difficulties are more established and harder to change, and have rarely included fathers. We are conducting a trial of a psychological intervention delivered to families with very young children, engaging both parents where possible.This study is a two-arm, parallel group, researcher-blind, randomized controlled trial, to test the clinical effectiveness and cost-effectiveness of a parenting intervention, Video Feedback Intervention to Promote Positive Parenting and Sensitive Discipline (VIPP-SD) for parents of young children (12-36 months) at risk of behavioural difficulties. VIPP-SD is an evidence-based parenting intervention developed at Leiden University in the Netherlands which uses a video-feedback approach to support parents, particularly by enhancing parental sensitivity and sensitive discipline in caring for children. The trial will involve 300 families, who will be randomly allocated into either an intervention group, who will receive the video-feedback intervention (n = 150), or a control group, who will receive treatment as usual (n = 150). The trial will evaluate whether VIPP-SD, compared to treatment as usual, leads to lower levels of behavioural problems in young children who are at high risk of developing these difficulties. Assessments will be conducted at baseline, and 5 and 24 months post-randomization. The primary outcome measure is a modified version of the Preschool Parental Account of Child Symptoms (Pre-PACS), a structured clinical interview of behavioural symptoms. Secondary outcomes include caregiver-reported behavioural difficulties, parenting behaviours, parental sensitivity, parental mood and anxiety and parental relationship adjustment. An economic evaluation will also be carried out to assess the cost-effectiveness of the intervention compared to treatment as usual.If shown to be effective, the intervention could be delivered widely to parents and caregivers of young children at risk of behavioural problems as part of community based services.ISRCTN Registry: ISRCTN58327365 . Registered 19 March 2015.